PENGARUH HARGA, PROMOSI DAN MEREK TERHADAP PENJUALAN BARANG PHARMASI DI PT. ANUGRAH PHARMINDO LESTARI - Maduretno Widowati (STIE Pelita Nusantara Semarang, 2010)
Amount of sales PT. Anugrah Pharmindo Lestari Semarang from 2001 till 2007 showed no positive trend. That between the realization of sales every year and target couldn’t be achieved. So the managers needs to know variable related to marketing for getting increasing of sales volume. Marketing activity not only activities to selling goods and services to consumers but also activities to know what the consumers wants.This research has been implemented on February 2008. There were 98 agents of PT. Anugrah Pharmindo Lestari in central java are chosen as the object of the research. Data analysis carried out by spread of the questioner to the object of research. The research hypothesis were tested by using classical assumption, multiple regression, T-test, F-test and also coefficient of determination (R2). The result of this research show that Price, Promotion, and brand in simultaneous having significantly affected to sales